2002
DOI: 10.1046/j.1537-2995.2002.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

PCR with sequence‐specific primer‐based simultaneous genotyping of human platelet antigen‐1 to ‐13w

Abstract: An extended, streamlined PCR-SSP protocol for simultaneous genotyping of HPA-1 to HPA-13w was established. This allows fast and reliable diagnosis of alloimmune thrombocytopenia, and is readily applicable to large-scale genetic population studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
27
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(36 citation statements)
references
References 35 publications
8
27
1
Order By: Relevance
“…In this study, no HPA-1b/1b homozygote was found, which is consistent with previous studies in Taiwan groups [18, 19]. Only nine individuals were found to be HPA-1a/1b heterozygous.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this study, no HPA-1b/1b homozygote was found, which is consistent with previous studies in Taiwan groups [18, 19]. Only nine individuals were found to be HPA-1a/1b heterozygous.…”
Section: Discussionsupporting
confidence: 92%
“…These data likely explain the low incidence of FNAIT and PTP due to HPA-1 alloimmunization in Taiwanese. We identified two homozygous b/b genotype individuals for HPA-2, a new observation for Taiwan [18, 19]. Although there is no report of HPA-2 involvement in alloimmune disorders in Taiwan, it may possibly play a more important role than does HPA-1.…”
Section: Discussionmentioning
confidence: 93%
“…Sequence Specific Primers (SSPs) were used for the genotyping of the HPA-3 (alleles: HPA-3a and HPA-3b) polymorphisms as described previously [11]. PCR cycling conditions were the following: After denaturation for 11 min at 95°C the amplification cycle (denaturation step at 95°C for 30 s, annealing step at 63°C for 30 s and extension step at 74°C for 30 s) was repeated 32 times and followed by final extension for 10 min at 74°C.…”
Section: Genomic Dna Analysismentioning
confidence: 99%
“…Sequence-specific primers (SSPs) were used for the genotyping as described previously. 8 Allelespecific primer sequences used for HPA-3 polymorphisms were: HPA-3a (5 0 -GGG GGA GGG GCT GGG GA-3 0 ), HPA-3b (5 0 -GGG GGA GGG GCT GGG GC-3 0 ), and HPA-3 common (5 0 -GAC CTG CTC TAC ATC CTG GA-3 0 ). Specific primers amplifying a fragment of human growth hormone (HGH) were used as positive controls: HGH-A (5 0 -TGC CTT CCC AAC CAT TCC CTT A-3 0 ) and HGH-B (5 0 -CCA CTC ACG GAT TTC TGT TGT GTT TC-3 0 ).…”
Section: Genotyping Protocolsmentioning
confidence: 99%